Validity of Fine Needle Aspiration Cytology in Diagnosis of Prostatic Lesions and Correlation with Trucut Biopsy - Thangaiah, MD, Judith J.; Balachandran, MD, Krishna; Poothiode, MD, Usha; Bhat, MD, Suresh (North American Journal of Medicine and Science, 2014)
Prostate fine needle aspiration (FNA) is an easy-to-perform outpatient procedure requiring no expensive equipment or anesthesia. The aim of this study was to analyze the cytomorphology of prostatic lesions and to correlate the findings in cytology with that of the histopathological appearance. In doing so we also assessed the diagnostic accuracy of fine needle aspiration cytology and identified possible pitfalls. The study was carried out in 100 patients who underwent tru-cut biopsy in the department of Urology at Kottayam Medical College, India during the period spanning from March 2010 to March 2011. Fine needle aspiration cytology (FNAC) was done with Franzen needle and followed by tru-cut biopsy after which the results of both were compared. FNAC gave a benign diagnosis in 64 cases and identified a malignant pattern in 36 cases. The overall accuracy of FNAC in this series in diagnosing prostatic lesions was 97% with a sensitivity of 100% and specificity of 95.5%. This shows that FNAC prostate is a reliable, relatively painless tool, which can be used for the diagnosis of prostatic carcinoma, especially in patients with high risk complications such as bleeding and infections in whom a tru-cut biopsy is more invasive. In addition it is also cost-effective and may sample a larger area.